Striking a balance: promoting quantity and quality of participation in Para sport - Walters, A.; Lawson, J.; Latimer-Cheung, A. E.; Davey, J. (Talent development in Paralympic sport: Researcher and practitioner perspectives, 2022)
This chapter is meant to serve as an introduction to quality participation across Para sport contexts. Quality participation - the positive subjective perceptions an athlete has of their experiences in sport over time, is proposed as a determinant of athlete well-being and sustained involvement in sport. In this chapter, quality participation is described and illustrated within different sport contexts: from playground to podium. Additionally, we provide strategies stakeholders (e.g., coaches, disability sports organizations) can use to facilitate quality participation, and where they can go to learn more about introducing quality participation into their coaching and organizational practices.